Pengaruh Digital Marketing dan Brand Image terhadap Keputusan Pembelian pada Haka Dimsum di Margonda - Raisa Aulia Sabela (Indo Publishing, 2026)
The development of modern marketing has undergone changes that rely on digital platforms as the main medium for communication between producers and consumers. This study aims to analyze the influence of Digital Marketing and Brand Image on purchasing decisions at Haka Dimsum in Margonda. The research uses a quantitative method with purposive sampling technique on 96 respondents determined using the Lemeshow formula. Data were collected thru an online questionnaire and analyzed using SPSS version 26 with validity tests, reliability tests, classical assumptions, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The research results show that Digital Marketing and Brand Image, both partially and simultaneously, have a positive and significant effect on purchasing decisions. The better the implementation of Digital Marketing and the stronger the Brand Image, the higher the consumer purchase decision for Haka Dimsum products in Margonda.